56 ANALISIS USAHATANI CABAI ( Capsicum Annum L ) DI DESA RIMBA TERAP KECAMATAN BETUNG KABUPATEN BANYUASIN (JASEP, 2017)
The study "Farming Analisasi Chilli (Capsicum annuum L) (Case Chilli Farmers in the village of Woods remains the District Banyuasin) aims to menganalisasi opinion and chili farm profit levels and contributing to the family income of farmers. The research was conducted in the village of Rimba Terap District of Betung Banyuasin. The method used in this study is a survey of farmers who undertake farming with monoculture system with random sampling is simple, whereas the method used in anlisasi data using the formula of income, to calculate the level of profit using the formula R / C ratio and for calculating the contribution of farming percentage formula used. The results showed that chili farming land size of 0.29 hectares with an average farm income chili Rp. 23.669 million, - / ha / Mt or Rp. 6.86401 million, - / Lg / MT. Chili farming profitable with a value of R / C = 1.72 with a contribution of 28.60% to the income of farming families.